The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.29210/3003673000
|View full text |Cite
|
Sign up to set email alerts
|

The mediating role of organizational learning in the relationship between organizational commitment and lecturer innovative behavior

Abstract: Innovation is one of the basic assets needed for organizations to survive<em> </em>in a competitive environment. Organizations such as higher education also need strong innovation in order to continue to compete and produce high-quality graduates. This study aims to analyze the factors that influence the innovative behavior of lecturers, especially based on organizational learning and organizational commitment. The research was conducted at STIK-PTIK with a sample of 108 lecturers who were taken ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 18 publications
(21 reference statements)
1
2
0
Order By: Relevance
“…The need to simultaneously adapt to the present circumstances and reimagining the future demands that organisational leaders adopt paradoxical thinking and action all the time. The study results confirm earlier findings that have reported intimate links between organisational learning capabilities and innovative behaviour (Khaki et al , 2017; Wahyuni et al , 2021; also see Alegre et al , 2012; Onağ et al , 2014; Urban and Gaffurini, 2017).…”
Section: Discussionsupporting
confidence: 91%
“…The need to simultaneously adapt to the present circumstances and reimagining the future demands that organisational leaders adopt paradoxical thinking and action all the time. The study results confirm earlier findings that have reported intimate links between organisational learning capabilities and innovative behaviour (Khaki et al , 2017; Wahyuni et al , 2021; also see Alegre et al , 2012; Onağ et al , 2014; Urban and Gaffurini, 2017).…”
Section: Discussionsupporting
confidence: 91%
“…Some scholars (Bunce & West, 1995;Janssen, 2000;Scott & Bruce, 1994;Messmann & Mulder, 2020) advocate the unidimensionality of IWB, which is criticized by others advancing its multidimensionality. Some (Zainal & Mohd Matore, 2021); organizational learning and organizational commitment (Wahyuni et al, 2021); well-being (Ibrahim et al, 2021); hope (Namono et al, 2021); human resource practices (Zreen et al, 2021); digital learning orientation and readiness for change (Aboobaker & Zakkariya, 2021); reflection (Messmann & Mulder, 2015); and leadership style (Khan et al, 2020). Although these studies hint at the importance of job autonomy and exposure to inno- anywhere and anyhow (Moll, 2015).…”
Section: Innovative Work Behaviourmentioning
confidence: 99%
“…Despite the importance of IWB in higher education institutions, studies have only recently tried to identify the predictors and determinants thereof, such as job autonomy, reward and recognition and work engagement (Dixit & Upadhyay, 2021); job autonomy and job commitment (Baharuddin et al, 2019); management support and exposure to innovation (Lambriex‐Schmitz et al, 2020b); teachers' self‐efficacy and school administrators' transformational leadership practices (Zainal & Mohd Matore, 2021); organizational learning and organizational commitment (Wahyuni et al, 2021); well‐being (Ibrahim et al, 2021); hope (Namono et al, 2021); human resource practices (Zreen et al, 2021); digital learning orientation and readiness for change (Aboobaker & Zakkariya, 2021); reflection (Messmann & Mulder, 2015); and leadership style (Khan et al, 2020). Although these studies hint at the importance of job autonomy and exposure to innovation among other factors as key predictors of IWB, none explore how compulsory NWW practices during COVID‐19 are related to faculty members' IWB in higher education institutions.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Based on the definition of organizational commitment, we can confirm that there is a positive relationship between organizational commitment and employees' innovative behaviors (Jafri, 2010). Wahyuni et al (2021) found that organizational learning and organizational commitment have a positive direct impact on innovative behavior. According to the discussion above, the following hypothesis was derived in this study: H4: Organizational commitment plays a mediating role between pay satisfaction and innovative behavior.…”
Section: Mediating Role Of Organizational Commitmentmentioning
confidence: 72%